2019
DOI: 10.1186/s13002-019-0339-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant leaves for wrapping zongzi in China: an ethnobotanical study

Abstract: BackgroundZongzi, a common Chinese rice-pudding and one of the most symbolic foods in traditional Chinese festivals, is integral to both Chinese traditional culture and daily meals. Traditionally, the leaves of different plant species have been used to wrap zongzi. The variety of zongzi leaves (ZLs) can contribute to the zongzi-based cultural diversity. Given the cultural and dietary significance of zongzi, the ethnobotanical surveys were carried out, aiming to investigate the diversity of plant species and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Like other linguistic groups, the Miao people also have the custom of collecting medicinal plants for cooking and bathing on the Dragon Boat Festival (the fifth day of the fifth month in the lunar calendar), including Acorus calamus , Dipsacus asperoides , Paederia scandens, and Leonurus artemisia . Many plants are harvested in the season around the Dragon Boat Festival [ 37 ], and thus it is the most prosperous time on Kaili medicinal market.…”
Section: Discussionmentioning
confidence: 99%
“…Like other linguistic groups, the Miao people also have the custom of collecting medicinal plants for cooking and bathing on the Dragon Boat Festival (the fifth day of the fifth month in the lunar calendar), including Acorus calamus , Dipsacus asperoides , Paederia scandens, and Leonurus artemisia . Many plants are harvested in the season around the Dragon Boat Festival [ 37 ], and thus it is the most prosperous time on Kaili medicinal market.…”
Section: Discussionmentioning
confidence: 99%
“…One species is a shrub; Dillenia suffruticosa and one species is a climber; Nepenthes ampullaria. This study recorded more plant species that were tree compared to the study conducted by Lin et al (2019) in China which reported that most plant habit used as plant-based food wrapper were herb followed by trees and no presence of shrub or climber were documented. Based on the preliminary interview, the tree is usually chosen because of its availability in the forest where no cultivation is needed.…”
Section: Diversity Of Plant-based Food Wrappermentioning
confidence: 45%
“…Respondents also informed that leaves need the shortest time to prepare compared to other parts which also can help to shorten the cooking time. Many previous studies have been reported regarding the use of plant leaves to wrap food in many countries and regions (Lin et al, 2019). In addition, leaves such as banana leaves are commonly used due to their flexibility, and durability, and can be folded easily (Harijati et al, 2013).…”
Section: Diversity Of Plant-based Food Wrappermentioning
confidence: 99%
“…During the Dragon Boat Festival, people often hang A. calamus and Artemisia argyi ( ai in Chinese) together on the front door to protect family members from evil. Different ethnic groups use A. calamus for different purposes, such as cleaning water, repelling mosquitoes and wrapping zongzi ( Shu et al, 2018 ; Lin et al, 2019 ). The majority of the Dulong will grow A. calamus in their home gardens to get a ready sufficiently of the medicine, and for ornamental and cultural value.…”
Section: Resultsmentioning
confidence: 99%